2012
DOI: 10.1200/jco.2011.37.1989
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ovarian Failure and Fertility in Long-Term Survivors of Hodgkin's Lymphoma: A European Organisation for Research and Treatment of Cancer Lymphoma Group and Groupe d'Étude des Lymphomes de l'Adulte Cohort Study

Abstract: Nonalkylating chemotherapy carries little to no excess risk of POF. Dose-response relationships for alkylating chemotherapy and age at treatment are both linear. Timely family planning is important for women at risk of POF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 27 publications
2
68
1
1
Order By: Relevance
“…The cumulative risks for premature ovarian failure are much higher after alkylating agent-based chemotherapy. 88,89 In a large cohort of women treated between the ages of 15 and 40 years for HL, the cumulative risk of premature ovarian failure after alkylating agent-based chemotherapy was 60% compared to only 3% or 6% after non-alkylating agentbased chemotherapy. 89 Independent risk factors for acute ovarian failure include increasing RT doses to the ovaries and exposure to procarbazine and cyclophosphamide at 13 to 20 years of age.…”
Section: Impact Of Cancer and Its Treatment On Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative risks for premature ovarian failure are much higher after alkylating agent-based chemotherapy. 88,89 In a large cohort of women treated between the ages of 15 and 40 years for HL, the cumulative risk of premature ovarian failure after alkylating agent-based chemotherapy was 60% compared to only 3% or 6% after non-alkylating agentbased chemotherapy. 89 Independent risk factors for acute ovarian failure include increasing RT doses to the ovaries and exposure to procarbazine and cyclophosphamide at 13 to 20 years of age.…”
Section: Impact Of Cancer and Its Treatment On Fertilitymentioning
confidence: 99%
“…88,89 In a large cohort of women treated between the ages of 15 and 40 years for HL, the cumulative risk of premature ovarian failure after alkylating agent-based chemotherapy was 60% compared to only 3% or 6% after non-alkylating agentbased chemotherapy. 89 Independent risk factors for acute ovarian failure include increasing RT doses to the ovaries and exposure to procarbazine and cyclophosphamide at 13 to 20 years of age. 82 An analysis of 590 women who were diagnosed with HL before age 18 showed that RT to the pelvis was associated with decreased incidence of parenthood (hazard ratio [HR], 0.66; 95% CI, 0.48-0.90; P=.01).…”
Section: Impact Of Cancer and Its Treatment On Fertilitymentioning
confidence: 99%
“…Alkylating agent-based chemotherapy is associated with a higher risk of premature ovarian failure compared with chemotherapy with non-alkylating agent-based chemotherapy. 40 The guidelines recommend fertility preservation (semen cryopreservation in male patients, ovarian tissue or oocyte cryopreservation in female patients) before the initiation of chemotherapy with alkylating agents or pelvic RT. 41,42 Oophoropexy should be considered to preserve ovarian function in premenopausal women if pelvic RT is contemplated.…”
Section: Treatment Guidelines Diagnosis and Workupmentioning
confidence: 99%
“…A legsúlyosabb ivarsejt-károsodást az alkilálószerek (például: cyclophosphamid, clorambucil) okozzák, azonban az antimetabolitok (methotrexat, 5-FU) szintén rendelkeznek gonadotoxikus hatással [2].…”
unclassified